Protocol for Management of Hyperthyroidism by Radioactive Iodine (RAIT)-SNMB Guidelines - Begum, Fatima; Sultana, Sadia; Nahar, Nurun; Alam, Faridul; Hasan, Mizanul; Hussain, Raihan; Haque, Mahmubul; Nasreen, Faria; Khan, Mohafizul Haque; Nisa, Lutfun; et al. (Bangladesh Journal of Nuclear Medicine, 2017)
Abstract not available Bangladesh J. Nuclear Med. 18(1): 85-88, January 2015